PSYCHOLOGICAL FEATURES OF PROTECTING ADOLESCENTS FROM INFORMATION THREATS IN THE CONTEXT OF GLOBALIZATION. - Sharipova Nilufar Asadovna. (Scholar Express Journal, 2023)
In an era defined by globalization and digital connectivity, adolescents are exposed to an unprecedented influx of information from various sources. While this exposure can be beneficial for their education and personal development, it also presents a significant challenge in terms of protecting them from information threats. This article explores the psychological features that play a crucial role in safeguarding adolescents from these threats. It delves into the impact of globalization on information access and the unique vulnerabilities that adolescents face in the digital age.The article also discusses strategies for parents, educators, and policymakers to help adolescents navigate the complex landscape of information while fostering digital literacy and cybersecurity skills.
Keywords: Adolescents; information threats; globalization; psychological features